Studies on the establishment of connections among spoken statements: what can they contribute to the promotion of students’ construction of a coherent discourse representation? - Yomha Cevasco, Jazmin (2013)
The aim of this article is to provide an overview of how the establishment of discourse connections among spoken statements has been studied by approaches to discourse analysis and psycholinguistic studies, in order to highlight what variables appear to be important for understanding how comprehension of spoken discourse can be facilitated. The consideration of discourse analysis approaches allows us to think about the role of the establishment of discourse connections among speech acts in the classroom, the uses of contextualization cues by bilingual students, the identification of social and cultural notions in teachers’ discourse, and the interactional effects of teachers’ interventions. Preliminary psycholinguistic studies contribute to our understanding of the role of establishing causal connections and integrating adjacent statements through the presence of discourse markers in the comprehension of spoken discourse by college students. The results of these approaches and studies provide insight into students’ comprehension of classroom discourse, and hold the potential for implications for instruction.